Kesantunan dalam percakapan film garis waktu Karya Fiersa Besari - Ratna Cahyaningtyas; Astuty Astuty; Herpindo Herpindo (Aksara: Jurnal Bahasa dan Sastra, 2023)
The research entitled "Politeness in Conversation from Fiersa Besari's Garis Waktu Film" is motivated by the occurrence of misunderstandings between speakers and speech partners, causing speech participants to feel offended by the speech received. This is because the speech participants pay less attention to matters relating to the principle of language politeness. The gap between this research and other research is that this research examines compliance and violation based on the six maxims of language politeness according to Leech and analyzes the compliance and violation from the point of view of the speech partner's acceptance as a measure of whether the speech conveyed by the speaker complies with or violates the principle of language politeness based on Yule's 'face' theory. This study aims to obtain a description of the form of compliance and violation of the principle of language politeness in the conversation of the movie Timeline by Fiersa Besari. The method used is descriptive qualitative. The researcher uses the listening method followed by the note-taking technique to collect data, while to analyze the data the researcher uses the commensurate method followed by the Pilah Elemen Penentu (PUP) technique. The result of this research shows 46 data. All data are divided into 31 data of the principle of language politeness compliance which includes maxims (1) praise, (2) generosity, (3) humility, (4) sympathy, and (5) agreement. Then 15 data of violations of the principles of language politeness which include maxims (1) praise and (2) agreement. The results of this study can be applied in class VIII learning with KD 3.16. This research only focuses on the compliance and violation of the principles of language politeness in the conversation of the movie Timeline, further researchers can develop an analysis of the causal factors and language politeness strategies.Â Keywords: context, form of speech, politeness principles